Microscale flow dynamics of red blood cells in a circular microchannel - Lima, R. (2011)
The blood flow dynamics in microcirculation depends strongly on the motion, deformation and interaction of RBCs within the microvessel. This paper presents the application of a confocal micro-PTV system to track RBCs through a circular polydimethysiloxane (PDMS) microchannel. This technique, consists of a spinning disk confocal microscope, high speed camera and a diode-pumped solid state (DPSS) laser combined with a single particle tracking (SPT) method. By using this system detailed motions of individual RBCs were measured at a microscale level. Our results showed that this technique can provide detailed information about microscale disturbance effects caused by RBCs in flowing blood.